2014
DOI: 10.1186/1471-2407-14-209
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of D2 lymphadenectomy and surgical quality control (KLASS-02-QC): a prospective, observational, multicenter study [NCT01283893]

Abstract: BackgroundExtended systemic lymphadenectomy (D2) is standard procedure for surgical treatment of advanced gastric cancer (AGC) although less extensive lymphadenectomy (D1) can be applied to early gastric cancer. Complete D2 lymphadenectomy is the mandatory procedure for studies that evaluate surgical treatment results of AGC. However, the actual extent of D2 lymphadenectomy varies among surgeons because of a lacking consensus on the anatomical definition of each lymph node station. This study is aimed to devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(48 citation statements)
references
References 14 publications
0
48
0
Order By: Relevance
“…Among the remaining articles, 19 studies [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] were excluded because EGC cases were mixed with AGCs in the cohort studies and data on AGCs were not extractable. Eight studies were further deleted for the following reasons: 2 studies were ongoing randomized controlled trials (RCTs) that only described study design and patient enrollment criteria without results reported [56,57]; 2 studies had overlapped enrollments with former research [58,59]; 1 study reported incomplete data that were not suitable for analysis [60]; and 3 studies discussed other issues irrelevant to the topic of this meta-analysis [61][62][63]. Finally, a total of 26 studies that compared the short-term and/or long-term results of AGCs treated by LG with those of OG were included .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the remaining articles, 19 studies [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55] were excluded because EGC cases were mixed with AGCs in the cohort studies and data on AGCs were not extractable. Eight studies were further deleted for the following reasons: 2 studies were ongoing randomized controlled trials (RCTs) that only described study design and patient enrollment criteria without results reported [56,57]; 2 studies had overlapped enrollments with former research [58,59]; 1 study reported incomplete data that were not suitable for analysis [60]; and 3 studies discussed other issues irrelevant to the topic of this meta-analysis [61][62][63]. Finally, a total of 26 studies that compared the short-term and/or long-term results of AGCs treated by LG with those of OG were included .…”
Section: Resultsmentioning
confidence: 99%
“…Laparoscopic gastrectomy has long been used to treat EGC, and in the past decade, attention has been paid to the feasibility and safety of LG for AGC. Although several clinical trials have been initiated to evaluate the effectiveness of LG [9,10,56,57], currently we do not have enough evidence to support this surgical procedure in AGC management. To this end, we conducted this meta-analysis trying to find some clues.…”
Section: Discussionmentioning
confidence: 99%
“…For early gastric cancer, laparoscopic gastrectomy and lymph node dissection is considered safe and comparable procedure in terms of postoperative outcome even in large scale randomized clinical trial, and also expected to show promising long-term survival outcome (2)(3)(4). Technically, laparoscopic gastrectomy may be feasible and gradually standardized even for advanced gastric cancer (5).…”
Section: Introduction For Single-incision Laparoscopic Surgery (Sils)mentioning
confidence: 99%
“…A recent paper that described the standardization of D2 lymphadenectomy and surgical quality control used the term 'exposure of vessels' to describe suprapancreatic lymphadenectomy (15). However, previous reports have not distinguished between the preservation and removal of periarterial tissues.…”
Section: Discussionmentioning
confidence: 99%